Pre-processing and classification of airborne hyperspectral data for wetlands mapping - Lau, Alvin Meng Shin (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Master of Science (Remote Sensing)) - Universiti Teknologi Malaysia, 2004